Multifunctional Nanosystems Powered Photodynamic Immunotherapy - Ma, Yunong; Xiao, Fengfeng; Lu, Cuixia; Wen, Liewei (Frontiers in Pharmacology, 2022)
Photodynamic Therapy (PDT) with the intrinsic advantages including non-invasiveness, spatiotemporal selectivity, low side-effects, and immune activation ability has been clinically approved for the treatment of head and neck cancer, esophageal cancer, pancreatic cancer, prostate cancer, and esophageal squamous cell carcinoma. Nevertheless, the PDT is only a strategy for local control of primary tumor, that it is hard to remove the residual tumor cells and inhibit the tumor metastasis. Recently, various smart nanomedicine-based strategies are developed to overcome the barriers of traditional PDT including the drawbacks of traditional photosensitizers, limited tissue penetrability of light, inefficient induction of tumor cell death and tumor resistance to the therapy. More notably, a growing number of studies have focused on improving the therapeutic efficiency by eliciting host immune system with versatile nanoplatforms, which heralds a broader clinical application prospect of PDT in the future. Herein, the pathways of PDT induced-tumor destruction, especially the host immune response is summarized, and focusing on the recent progress of nanosystems-enhanced PDT through eliciting innate immunity and adaptive immunity. We expect it will provide some insights for conquering the drawbacks current PDT and expand the range of clinical application through this review.